Effectiveness of interprofessional education in renal physiology curricula for health sciences graduate students - Harrison-Bernard, Lisa M. (Adv Physiol Educ, 2017)
The primary purpose of conducting an interprofessional education (IPE) experience during the renal physiology block of a graduate-level course was to provide basic science, physical therapy, and physician assistant graduate students with an opportunity to work as a team in the diagnosis, treatment, and collaborative care of a patient with acute kidney injury. The secondary purpose was to enhance the understanding of basic renal physiology principles with a patient case presentation of renal pathophysiology. The overall purpose was to assess the value of IPE integration within a basic science course by examining student perceptions and program evaluation. Graduate-level students operated in interprofessional teams while working through an acute kidney injury patient case. The following Interprofessional Education Collaborative subcompetencies were targeted: Roles/Responsibilities (RR) Behavioral Expectations (RR1, RR4) and Interprofessional Communication (CC) Behavioral Expectations (CC4). Clinical and IPE stimulus questions were discussed both within and between teams with assistance provided by faculty facilitators. Students were given a pre- and postsurvey to determine their knowledge of IPE. There were statistically significant increases from pre- to postsurvey scores for all six IPE questions for all students. Physical therapy and physician assistant students had a statistically significant increase in pre- to postsurvey scores, indicating a more favorable perception of their interprofessional competence for RR1, RR4, and CC4. No changes were noted in pre- to postsurvey scores for basic science graduate students. Incorporating planned IPE experiences into multidisciplinary health science courses represents an appropriate venue to have students learn and apply interprofessional competencies.